Responding to unethical research: the importance of transparency - Rogers, A. (Journal of medical ethics, 2020)
We thank Goldstein and Peterson, Caplan, and Bramstedt for engaging with our paper on the ethics of publishing and using Chinese transplant research that involves organs procured from executed prisoners.1-4 In that paper, we examine consequentialist and deontological arguments for and against using data from unethical research.Goldstein and Peterson question the relationship between the social and scientific value of the research and the decision to publish the results. They argue that the failure to publish scientifically valid and socially valuable Chinese transplant research results in potential repetition of the research and subsequent exposure of new participants to research risks for data that already exists. This argument has intuitive appeal, in both its positive form (the data are already there so let’s use them) and negative form (by not using the data we subject future participants to avoidable research risks).Prima facie, failure to use the data does seem to breach a fundamental principle of research ethics, that of only exposing people to risks in research to produce novel and socially valuable knowledge. However, this point relies heavily on the assumption that data from unethical research are valid and valuable. This is a useful assumption to make in a theoretical argument as it clarifies the challenge of weighing up the potential utility of the …